PENGARUH BUDAYA ORGANISASI TERHADAP PERILAKU INDIVIDU PADA KANTOR PERTANAHAN KABUPATEN TABALONG - Yuzan Noor (Jurnal PubBis, 2018)
This research aims to find out how much influence organizational culture toward individual behavior by testing the hypothesis that organizational culture effect significantly to individual behavior. The sampling technique used was total sampling, as many as 30 respondents. The research approach is quantitative statistics. Methods of analysis used is simple with the help of regression software SPSS 19. Based on research results, note that the organizational culture at the Land Office Tabalong Regency in General is very powerful and influential positive individual behavior towards members of the organization. This is reflected from the level of individual behavior is generally high. The value of the variable correlation organizational culture toward individual behavior is a significant variable with a value of r = 0.694. The result of the Adjusted R Square retrieved number 0.463 or large influence organizational culture toward individual behavior is 46%. Keywords: organizational culture; individual behavior